Paspalum lilloi - Reutemann, Anna Verena (2022)
Paspalum lilloi.With all the information compiled, this is a range-restricted species, known from 1 location in the Iguazu Waterfalls, in northeastern Argentina and southern Brazil. Its extent of occurrence (EOO) and area of occupancy (AOO) are 8 km². It is a reophile and rupicole species, well adapted to fast stream rivers and waterfalls. In the past, its EOO and the number of subpopulations declined due to habitat loss caused by human settlements, leading to the putative local extinction of a Paraguayan subpopulation; nowadays the main threat to its habitat is river-flow fluctuation caused by rainfall regimes and dam constructions. Fortunately, the remnant subpopulations are circumscribed in two protected areas belonging to the National Park of Iguazú in Misiones (Argentina) and the National Park of Iguaçú in Paraná (Brazil), but this cannot protect the species against continuing habitat decline due to river-flow fluctuation. The species is listed as Critically Endangered (CR).